Toxicity reduction evaluation protocol for municipal wastewater treatment plants - Botts, John A.; Braswell, Jonathan W.; United States. Environmental Protection Agency. Office of Research and Development (Cincinnati, Ohio. : United States Environmental Protection Agency, 1989)
55